Generalization and propagation of spiraling Bessel beams with a helical axicon - 孙琼阁 周可雅 方光宇 刘正君 刘树田 (Chinese physics B, 2012)
A generalized type of spiral Bessel beam has been demonstrated by using a spatially displaced helical axicon （HA）. The topological charge of the spiraling Bessel beams is determined by the order of the input Laguerre Gaussian （LG） beam and the topological charge of the HA. The obtained spiraling Bessel beams have an LG type of modulation along their propagation direction and exhibit annihilation-reconstruction properties. Theoretical analysis is presented, including that of the stability, propagation distance, topological charge, and spiraling dynamic characteristics. The mathematical and numerical results show that the propagation distance and helical revolution of the spiraling Bessel beams can be controlled through choosing appropriate radius of the HA.